Long term outcome of patients with postinfarction left ventricular pseudoaneurysm. Issue 10 (15th September 2003) - Moreno, R; Gordillo, E; Zamorano, J; Almeria, C; Garcia-Rubira, J C; Fernandez-Ortiz, A; Macaya, C
Abstract : Background: It is debatable whether surgical repair is routinely indicated in asymptomatic patients with left ventricular pseudoaneurysms. Objective: To evaluate the long term outcome of patients with pseudoaneurysm after myocardial infarction, focusing on those treated conservatively. Methods: 10 patients with postinfarction left ventricular pseudoaneurysm were followed up over a mean (SD) period of 3.8 (5.2) years. Results: In those treated conservatively (n = 9), cumulative survival was 88.9 (10.5)% and 74.1 (16.1)% at one and four years, respectively. The probability of being free of cardiac death was 88.9 (10.5)% at both one and four years. No patient had complete fatal heart rupture during follow up. Three patients suffered ischaemic stroke (at 1, 11, and 62 months). The cumulative incidence of ischaemic stroke was 10% at one year and 32.5% at four years. Conclusions: Long term outcome of patients with postinfarction left ventricular pseudoaneurysm is relatively benign, with a very low risk (none in this series) of fatal rupture. Taking into consideration the relatively high risk of stroke, chronic anticoagulant treatment could be considered.